Faktor - Faktor Fundamental Terhadap Earning Per Share Pada Perusahaan Perbankan BUMN - Thomas Firdaus Hutahean; Fransisco Fransisco; Kelly Prasetyo; Surya Surya; Saut Maruli Tua Pandiangan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study is to obtain a bachelor's degree in Accounting. The study was used to find knowledge about 4 fundamental elements, namely DER, ROE, PER & PBV on EPS of banks verified on the IDX from 2018-2021. This study has a population of BRI, BUMN, BMRI, BNI and BTN whose reports have been on the IDX since 2018-2021. using a saturated sampling technique sample of 64 covering 4x16 (quarterly). The data uses a purposive sampling method and is collected using a file study technique using legacy studies, namely searching files, books and others, then collecting it from the internet, which includes quarterly financial data from 2018-2021 on BUMN on the IDX. The report is related to DER, ROE, PER & PBV. whose data is on the IDX. Keywords: Fundamental,Earning Per Share,Banking